The multilingual context as an extrinsic motivation factor for English language learning. A case study - Bozzo, Luisa (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Multilingualism is a natural condition for humans. Recent studies on multilingual education have demonstrated its worth in developing the cognitive abilities and the character of learners, in addition to framing intercultural minds, a must in our increasingly globalizing world. The learning context plays an essential role in the achievement of these objectives, constituting one of the main elements of extrinsic motivation for language learning. This study analyses the motivational factors of a specific multilingual environment, that of the Liceo Internazionale Europeo Statale “Altiero Spinelli” of Turin, Italy, where students are stimulated to learn foreign languages and the English language in particular. This high school has a peculiar curriculum, based on the “L1 Project” which regulates all educational aspects. The factors taken into consideration are the curricular objectives, the participants, the languages and nationalities involved, the pedagogical approach, the teaching and learning of the English language, and several dimensions of the extended context. The paper features the results in terms of English language learning, considers the strengths and the weaknesses of the programme and suggests some directions for the development of its teaching and the learning environment.